CAN ZAKAT AND PURIFICATION BE EMPLOYED IN PORTFOLIO MODELLING? - Retno Subekti; Abdurakhman Abdurakhman; Dedi Rosadi (Journal of Islamic Monetary Economics and Finance, 2022)
The Capital Asset Pricing Model (CAPM), which has interest rates in its specification, can be deemed non-Shariah compliant. Therefore, the sukuk rate has been proposed to replace these rates in CAPM. This study analyses portfolio modelling by involving two essential elements in Islamic principles, namely zakat and purification. The concept of purification has been applied in the Shariah stock selection process in Indonesia, while at the same time, zakat has been widely socialised in stock investment. The study highlights two models that consider the concept of zakat reduction and the purification factors for portfolios in the Indonesian stock market. According to the robustness tests conducted, the proposed Shariah-compliant asset pricing model developed in this study is valid. Zakat reduction and purification factor integration in mathematical models can be applied in portfolio modelling.